Analysis of vein grafting versus arteriovenous loop in microvascular head and neck reconstruction: Multicenter series of 36 patients. Issue 5 (8th March 2023) - Pak, Kaitlynne Y.; Anderson, Spencer R.; Langenfeld, Tyler L.; Tan, Kenneth; Slijepcevic, Allison; Wimalawansa, Sunishka; Ducic, Yadranko; Wax, Mark K.; Kadakia, Sameep P.
Abstract: Background: The utilization of an arteriovenous loop is an underreported technique that affords the creation of reliable vascular options. Understanding the efficacy and impacting variables of microvascular reconstruction with an arteriovenous loop can be critical to its use. Methods: Multi‐institutional study of 36 patients who underwent vein grafting or AV loop with free tissue transfer. Results: 58.3% of patients received prior radiation and 38.9% prior flap reconstruction. Flap success for vein grafting was 76% and AV loop was 100% ( p = 0.16). Success for the radiated cohort was 90.5% and non‐radiated 80% ( p = 0.63). Flap success for the radiated, vein grafted patient was 83.3% and 100% flap success rate for radiated, AV loop patient ( p = 0.49). Overall flap survival was 83.3% versus 97% overall success rate in the United States. Conclusion: The AV loop is a viable modality for vessel‐depleted free tissue reconstruction. Radiation and previous surgery do not significantly impact flap success rates.